(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: During the Ramadan fast, among Muslims due to change in life-style, in terms of obtaining the daily calorie intake via two meals with alteration of medication schedule or reduction in sleep duration, might affect patients with cardiovascular diseases. The aim of this study was to determine the proportion of cardiac patients who fasted and factors associated with breaking fast. Methods and materials: This cross-sectional study was conducted during the month of Ramadan 2018 (17 May to 15 June) in the outdoor and indoor of Cardiology Department of Chattogram Medical College Hospital, Chattogram, Bangladesh. Muslim patient, age above 18 years was included. Pregnant lady lactating mother and Non-Muslims patients were excluded. Data regarding age, sex, comorbid conditions, fasting status and reason for breaking fast if applicable were collected through a case record form and cardio vascular condition was evaluated. Results: Out of 221 patients, 121 (54.8%) were admitted in indoor and 100 (45.2%) patients attended in outdoor. Male to female ratio was equal (Male 103 and female 118) and mean (±SD) age was 53.48±12.22 years. Of those, 76 (73.8%) male and 86 (72.9%) female were fasting. Significantly higher number of female broke fast than male [Male 41 (53.9%) versus female 65 (75.6%). One hundred and twenty fasted patients (78.4%) experienced symptom aggravation and most of them (91.7%) had to break their fast. Aggravating symptoms were chest pain, breathlessness and hypoglycemic attack present respectively in 68.1%, 16.3% and 12.5% patients. Besides symptoms aggravation, other causes of breaking fast were medication in 36 (22.1%) patients and diagnostic procedure in 4 (2.47%) patients. Conclusion: Ramadan fasting had significant effect on female cardiac patients than male. Findings should be investigated with a prospective study. JCMCTA 2019 ; 30 (1) : 27-30